Meningkatkan Kemampuan Berpikir Kritis Siswa Pada Pembelajaran Tari Melalui Metode Team Games Tournament Kelas X Busana 2 SMK Negeri 27 Jakarta - Fajria, Lailatul; Ojang Cahyadi; B Kristiono Soewardjo (Jurnal Pendidikan Tari, 2024)
This study raises the problem that exists in class X Clothing 2 SMK Negeri 27 Jakarta, namely the lack of ability in students' critical thinking in dance learning. This problem occurs because the learning method at school has not led to activities that make students able to think critically, monotonous learning makes students bored. This study aims to improve students' critical thinking skills in dance learning through the Team Games Tournament (TGT) method in dance criticism material. This study used the Classroom Action Research (PTK) method from Kurt Lewin which was carried out in two cycles. Each cycle consists of four stages, namely Planning, Action, Observation, and Reflection. The research took place from February to May 2023 at SMK Negeri 27 Jakarta. Data was collected through a learning process in dance criticism material in 8 meetings for 2 cycles. Data collection techniques using observation techniques, interviews, and tests. The results showed that based on the results of the pre-cycle value of 46.6%, then cycle I increased to 71%, and cycle II to 86%. This can be interpreted that the application of the TGT learning method can significantly improve students' critical thinking skills. The conclusion of this study is that the TGT learning method has experienced a significant increase as evidenced by the learning outcomes using dance criticism material.